2010
DOI: 10.1016/j.tet.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective addition reactions at C-2 of 3,4-dihydropyrimidinones. Synthesis and evaluation of multifunctionalized tetrahydropyrimidines

Abstract: a b s t r a c tMultifunctionalized tetrahydropyrimidines derivatives have been synthesized from Biginelli 3,4-dihydropyrimidin-2-(1H)-thiones (DHPMs) efficiently. The transformation includes desulfurization of DHPMs with Raney-Ni and subsequent regioselective C-2 functionalization using a variety of C-nucleophiles with simultaneous activation with ethyl chloroformate. Functionalized pyrimidine derivatives containing bulky substituents at C-2 of the pyrimidine ring are cytostatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This compound was obtained as bright crystals (ethyl alcohol), white color, yield 92%, mp 240 C; IR: cm À1 3200 (NH); 1 H NMR: (2E)-2-(1,3-Benzothiazol-2-ylimino)-6-methyl-2,3-dihydropyrimidine-4(1H)-one (5). This compound was obtained as powder (ethyl alcohol), buff color, 82% yield, mp 305 C; IR: cm À1 3303, 3184 (2NH), 1691 (CO); 1 H NMR: (2E)-2-(1,3-Benzothiazol-2-ylimino)-6-phenyl-2,3-dihydropyrimidine-4(1H)-one (6).…”
Section: Types Of Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…This compound was obtained as bright crystals (ethyl alcohol), white color, yield 92%, mp 240 C; IR: cm À1 3200 (NH); 1 H NMR: (2E)-2-(1,3-Benzothiazol-2-ylimino)-6-methyl-2,3-dihydropyrimidine-4(1H)-one (5). This compound was obtained as powder (ethyl alcohol), buff color, 82% yield, mp 305 C; IR: cm À1 3303, 3184 (2NH), 1691 (CO); 1 H NMR: (2E)-2-(1,3-Benzothiazol-2-ylimino)-6-phenyl-2,3-dihydropyrimidine-4(1H)-one (6).…”
Section: Types Of Bacteriamentioning
confidence: 99%
“…Although a large number of dihydropyrimidinone (DHPM) derivatives have been prepared in a single‐pot Biginelli multi‐component reaction and its variants , very useful and convincing structural variability of these interesting heterocycles have been achieved through chemical functionalization of all the six positions around the DHPM core . Recently, it was reported that the C‐2 amine substituted pyrimidine derivatives have inhibited Mycobacterium tuberculosis as well as their inhibitory effect against the proliferation of some cell cultures. In a continuation of our efforts to synthesize small molecule heterocyclic compounds from modified guanidines and active methylene compounds , we are reporting in this study the synthesis of C2‐amino/imino benzothiazole substituted dipyrimidines, dihydropyrimidinones, and dihydroimidazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of wide spectrum biological activities such as anti allergic [2], antitumor [3], antipyretic [4], anti-inflammatory [4] and antiparasitic [5] activities, exhibited by synthetic pyrimidine based scaffolds, a number of analogues have garnered considerable attention. During a screening effort for antiviral agents, we found that multifunctionalized tetrahydropyrimidines derivatives bearing bulky C-2 alkyl substituents depict cytostatic activity and inhibit proliferation of murine leukemia, murine mammary carcinoma, human T-lymphocyte and human cervix carcinoma cells [6]. 3,4-Dihydropyrimidin-2-(1H)-ones (DHPMs) and their appropriately functionalized derivatives have interesting pharmacological profiles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of DHPM derivatives have been prepared in a single-pot Biginelli multi component reaction [8] (MCR) and its variants [9], very useful and convincing structural variability of these interesting heterocycles have been achieved through chemical functionalization of all the six positions around the DHPM core [10]. Recently, we reported [6] on the facile conversion of DHPMs into tetrahydropyrimidines. As part of an ongoing, multi-faceted program aimed toward development of small molecules as therapeutic agents, herein we report a straightforward conversion of Biginelli DHPMs into C-2 amine substituted pyrimidine derivatives and their screening as inhibitors of Mycobacterium tuberculosis and their inhibitory effect against the proliferation of some cell cultures.…”
Section: Introductionmentioning
confidence: 99%